2021
DOI: 10.22441/jdm.v4i2.12245
|View full text |Cite
|
Sign up to set email alerts
|

Studi Kelayakan Usaha Dan Strategi Pengembangan Budidaya Ikan Lele Di Kota Denpasar (Studi Kasus Petani Ikan Lele di Ubung Kaja)

Abstract: Objek penelitian di Kota Denpasar pada UMKM yang bergerak dibidang perikanan dengan membudidayakan ikan lele. Penelitian ini menggunakan metode studi kelayakan bisnis yang bertujuan untuk memperoleh gambaran yang lebih mendalam dari kelayakan suatu bisnis dari aspek SKB dengan cara analisis kualitatif dan analisis kuantitatif.  Menggunakan analisis SWOT meliputi NPV, IRR, PP, dengan cara wawancara dan observasi. Hasi penelitian menunjukan bahwa nilai (NPV) yaitu Rp. 10.829.000,00, Rp. 56.246.244,00, Rp. 100.50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Catfish that are ready for consumption are catfish that have a size between 18 cm to 20 cm with a weight per tail of 125 grams or even more than that (Putri Firdausi et al, 2024), in 1 kg of catfish contains 8 fish weighing 125 grams per tail (Bidayani et al, 2023) However, if the weight of catfish reaches 200 grams per tail then per kg only contains 5 to 6 fish (Astari et al, 2021). Catfish to reach consumption size requires a maintenance time of about 2 to 3 months with daily feeding.…”
Section: Fuzzy Logic Implementationmentioning
confidence: 99%
“…Catfish that are ready for consumption are catfish that have a size between 18 cm to 20 cm with a weight per tail of 125 grams or even more than that (Putri Firdausi et al, 2024), in 1 kg of catfish contains 8 fish weighing 125 grams per tail (Bidayani et al, 2023) However, if the weight of catfish reaches 200 grams per tail then per kg only contains 5 to 6 fish (Astari et al, 2021). Catfish to reach consumption size requires a maintenance time of about 2 to 3 months with daily feeding.…”
Section: Fuzzy Logic Implementationmentioning
confidence: 99%
“…Research conducted by (Wardana et al, 2014) with an analysis of financial feasibility and income contribution to a household income of catfish farming, further research conducted by Sudana et al (2013) analyzed the feasibility of African catfish farming and its effect on the income level of fish farmers, the result of this business is that the catfish is feasible to be cultivated in terms of financial, marketing and social aspects, these three aspects have a significant effect on farmers' income. Furthermore, Astari et al (2021) researched business feasibility analysis and development strategies for catfish farming from financial and nonfinancial aspects to determine the feasibility of the business from all aspects and not focus on financial aspects from a financial and non-financial perspective. Furthermore, research conducted by Mahyuddin et al (2014), which analyzed the feasibility and sensitivity of input prices in catfish farming, showed that the business was feasible to develop.…”
Section: Introductionmentioning
confidence: 99%